FRI0157 Remission in patients with rheumatoid arthritis treated with etanercept (with and without methotrexate) in routine clinical practice as compared to a clinical trial experience. (23rd January 2014) - Keystone, E.C.; Cannon, G.W.; Wang, B.C.; Park, G.S.; Koenig, A.; Collier, D.H.
Abstract : Background: The efficacy of etanercept (ETN), alone or in combination with the disease-modifying antirheumatic drug (DMARD) methotrexate (MTX), has been demonstrated in randomized clinical trials (RCTs) of patients with rheumatoid arthritis (RA). RCTs are conducted in select patient (pt) populations, and thus it is important to determine how findings from RCTs compare with clinical practice. Objectives: To compare remission rates among pts with RA initiating ETN therapy in routine clinical practice settings in the Rheumatoid Arthritis DMARD Intervention and Utilization Study (RADIUS II, a prospective observational study) with remission rates in the Trial of Etanercept and Methotrexate with Radiographic Patient Outcomes (TEMPO, a double-blind RCT). Methods: Pt demographics, baseline characteristics, disease activity over time, remission status, and time to remission were evaluated for pts initiating ETN (monotherapy or ETN+MTX). Continued remission (Clinical Disease Activity Index [CDAI] of ≤2.8 for ≥6 months with at least two observations within a continuous observation period) was determined through year 3 by treatment group and study. The remission rate was determined for differing levels of disease severity. Results: In TEMPO, 223 patients started ETN alone and 231 pts started ETN+MTX simultaneously. In RADIUS II, 1172 pts initiated ETN monotherapy and 2376 pts added ETN to established MTX (ETN+MTX). Pts in RADIUS II had lower disease activity at baseline (mean [SD] CDAI: 36 [13]) than those in TEMPO (CDAI: 47 [13], P<0.001). Most other clinical and demographic features (eg, age, rheumatoid factor, sex) were comparable at baseline. In each study, likelihood for CDAI remission and time to remission varied with baseline disease activity (Table 1 ). Generally, more patients with lower baseline CDAI scores achieved remission by year 3 in both trials than those with higher baseline CDAI scores (Table 1 ). There was a more rapid onset of CDAI remission in TEMPO than RADIUS II that may be explained in part by compliance, other pt differences, or in the case of combination therapy, simultaneous (rather than sequential) initiation of ETN+MTX. Conclusions: ETN, with or without MTX, effectively induced remission by year 3 in routine clinical practice as seen in a RCT. Pts with lower disease severity were more likely to reach remission. Differences in drug initiation sequence might limit the ability to compare ETN+MTX groups in RCTs versus real world. These analyses indicate that continued remission may be more likely in pts who reached remission earlier. Disclosure of Interest: E. Keystone Grant/Research support from: Immunex Corp, a wholly owed subsidiary of Amgen Inc; Wyeth, which was acquired by Pfizer in Oct 2009, G. Cannon Grant/Research support from: Immunex Corp, a wholly owed subsidiary of Amgen Inc; Wyeth, which was acquired by Pfizer in Oct 2009, B. Wang: None Declared, G. Park Shareholder of: Amgen Inc, Employee of: Amgen Inc, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Collier Shareholder of: Amgen Inc, Employee of: Amgen inc